Determinación de los niveles de iluminación de las áreas administrativas de la U.A CAREN – UTC para cumplir con las normas internacionales. cantón Latacunga. provincia de Cotopaxi. periodo 2013 - Jácome Naranjo, Daniel Eduardo (2014)
The correct lighting of working environment allows the human beings, in good conditions well-being visual, to do their job safe and productively, so it should be taken into account in designing, like that in the maintenance service. Inadequate lighting causes eyestrain, fatigue, headache, stress and accidents. The work with bit light damages the sight; also sudden light changes can be dangerous, because blind temporarily while the eye adapts to new lighting, the security degree that executes the work depends on the visual capacity, is why that to achieve a good level of visual comfort should be a balance among the quantity, quality and light stability, such get a lack of reflexes and flicker, lighting uniformity, lack of contrasts etc. All of them in visual function demands of work and personal characteristics….